RECONSTRUCTION NATIONAL SOCIAL SATISFACTION SYSTEM FOR HEALTH FIELD IN THE AUTONOMY REGION WITH VALUE OF WELFARE - Gunarto Gunarto (UNISSULA, 2017)
Objectives to be achieved in this research To understand and analyze the National Social Security System Construction of Health Sector in the current positive law, to understand and analyze the weaknesses of the National Social Security System in the Field of Health today and to analyze and reconstruct the National Social Security System for Health Based on the value of welfare Research is expected to have both theoretical and practical uses that researchers use is socio legal research, this research approach is chosen to see how far the effectiveness of law in the prosperity of the community especially in health insurance coverage, here the law is not only seen in terms of its effectiveness but Also related to non-legal factors such as institutions related to the welfare of the community. The Legal System of the Health Insurance Program with the participation of BPJS is still very weak both in terms of the legal substance component, in providing equitable welfare in obtaining health services through the Health Insurance Program with. Strengthening Components of Legal Substances by changing Article 39 Paragraphs (1), (3) and (4) of Presidential Regulation No. 12 of 2013, Strengthening Legal Structure Components by Strengthening FKTP I on the regulation of Government Regulation, Strengthening Legal Culture Component by developing Culture of community law through continuous education to the community so that the community, the Government is not responsible for providing funds for Beneficiaries of Contribution (PBI).